Quantitative Sharia-Screening Effect on Portfolio Performance and Volatility: Evidence from Indonesia - Syamsul Arifin; Ibnu Qizam (Global Review of Islamic Economics and Business, 2021)
The aim of this study is to examine the comparative performance and volatility between Sharia and conventional portfolios listed on the Indonesia Stock Exchange (IDX) and to investigate the effect of quantitative (debt-ratio) screening on the Sharia-and-conventional-portfolios returns specifically applied in the selected public firms with the inter-industrial low-correlations. Applying a non-parametric test, the autoregressive integrated moving average (ARIMA) model, and the regression analysis, the results suggest that there is no difference in performance between Sharia and conventional portfolios; Sharia portfolios show the lower risks than conventional portfolios. Using quantitative Sharia-screening, the debt-to-equity ratio (DER) affects Sharia-portfolio returns, but not conventional-portfolio returns. This study contributes to providing country-specific evidence on applying quantitative Sharia-screening. Taking notice of the existing high-profile debt-ratio and applying the relatively loose standard of quantitative Sharia-screening for the public firms in Indonesia, this suggests that a country-specific quantitative Sharia-screening standard should be supported.